Pengaruh Self-Efficacy Terhadap Motivasi Berprestasi Mahasiswa Jurusan Manajemen Berbasis KKNI - AYN Warsiki; Tri Mardiana (Eksos LPPM, 2020)
This study aims to find out how much self-efficacy can affect student achievement motivation. Achievement motivation is an impulse that is in a person to achieve success and avoid failure that leads to behavioral tendencies to maintain and enhance a success that has been achieved by referring to the benchmark of the best achievements ever achieved by both himself and others. So that achievement motivation also affects the choice of activities undertaken by someone. In the learning process, self-efficacy (self-efficacy) which is owned by someone can influence achievement motivation. Self-efficacy refers to belief in one's ability to organize and carry out the actions needed to manage the situation.